The Effect of Reading Logs on Students' Reading Comprehension Performance at SMPN 3 Timpah - Heriyanto, Chrizzya Ludwiqa; Asi, Natalina; Luardini, Maria Arina (IKIP Siliwangi, 2025)
Reading logs are a promising tool for improving reading comprehension by fostering engagement, reflection, and metacognitive skills. This research investigates the effect of reading logs on students’ reading comprehension performance and their perceptions of its use at SMPN 3 Timpah during the 2024/2025 academic year. Focusing on rural education, it explores how reading logs support comprehension of narrative, descriptive, and procedural texts, aiming to enhance performance scores. A quantitative one-group pretest-posttest design was employed, using pretests and posttests to measure comprehension and a Likert-scale questionnaire for secondary data. The study involved 55 students from grades 7, 8, and 9. Data analysis included paired sample t-tests for performance and descriptive statistics for opinions. Results indicated significant improvement in comprehension, with p-values of 0.000 across all grades. Average scores rose from 47.1 to 62.9 in grade 7, 61.3 to 75.1 in grade 8, and 62.2 to 75.6 in grade 9. Students credited reading logs for helping identify key concepts, expand vocabulary, and enhance summarization and analysis skills. Favorable questionnaire responses highlighted the tool’s user-friendly, organized nature and its ability to boost motivation, engagement, and critical thinking. This study underscores reading logs’ potential as an effective EFL instructional strategy.